THE ABERDARE FOREST PARADOX: CBNRM FOR SUSTAINABLE ECONOMIC UTILIZATION - Karanja, Grace Njeri (International Journal of Allied Research in Economics (IJARE), 2023)
Community-Based Natural Resource Management (CBNRM) is a dynamic concept that takes on different interpretations contingent upon geographical boundaries, socio-political dynamics, and bio-physical characteristics. This paper seeks to unravel the multifaceted dimensions of CBNRM, clarifying its essence in diverse contexts. In its essence, CBNRM is the collaborative stewardship of natural resources, encompassing land, forests, wildlife, and water sources, driven by local institutions and communities, with the ultimate aim of yielding localized benefits. By examining the intersections of CBNRM and sustainability, we aim to shed light on the crucial role of these community-driven initiatives in advancing economic sustainability and meeting the needs of present and future generations. The essence of CBNRM, as articulated by Armitage (2005), is rooted in the collective efforts of local institutions and communities, emphasizing the shared responsibility for preserving and managing vital natural resources. It is imperative to recognize that this concept takes on different hues across various geographical and socio-political landscapes, reflecting the unique challenges and opportunities inherent to each context. In a world characterized by increasing ecological pressures and resource depletion, the relevance of CBNRM as an avenue for local empowerment and resource conservation cannot be overstated. To contextualize the significance of CBNRM, we draw from the Brundtland Commission's (1987) definition of sustainability, which envisions development as a pursuit that not only satisfies the immediate needs of the current generation but does so without jeopardizing the ability of future generations to fulfill their own requirements. This conceptualization of sustainability extends beyond ecological considerations to encompass the socioeconomic aspects of sustainable development. Adams (2006) elucidates the economic dimension of sustainability, which entails the perpetual production of goods and services, enabling the management of debt and the maintenance of equilibrium across sectors, including agriculture and industry. The conceptual evolution of sustainability has been a product of rigorous discourse and international conferences, which have explored the intricate connection between the environment and development (Ochola, Sanginga, & Bekalo, 2010). It is within this context that we examine how CBNRM, with its emphasis on local control and collective action, plays a pivotal role in achieving sustainability goals, both at the community level and in the broader context of global environmental and development imperatives. This paper seeks to delve deeper into the dynamic interplay between CBNRM and sustainability, offering insights into how community-based natural resource management can serve as a catalyst for economic sustainability and environmental stewardship. By examining these facets, we hope to contribute to a nuanced understanding of the transformative potential of CBNRM in realizing the principles of sustainability on local and global scales.